VD_FINDINFO Jug / 2023 / 130 vom 26. August 2022 - VD Tribunal cantonal (2022)
LÉSION CORPORELLE, INJURE, CONTRAINTEDROIT PÉNAL, ENLÈVEMENTINFRACTION, ADMINISTRATION DES PREUVES, DÉFAUTCONTUMACE | 123 ch. 1 CP, 177 al. 1 CP, 180 al. 1 CP, 181 CP, 183 ch. 1 CP, 10 al. 1 CPP (CH), 131 al. 3 CPP (CH), 147 al. 1 CPP (CH), 366 CPP (CH), 389 CPP (CH)